Sugars, the clock and transition to flowering - Bolouri Moghaddam, Mohammad Reza; Van den Ende, Wim (Frontiers in Plant Science, 2013)
Sugars do not only act as source of energy, but they also act as signals in plants. This mini review summarizes the emerging links between sucrose-mediated signaling and the cellular networks involved in flowering time control and defense. Cross-talks with gibberellin (GA) and jasmonate (JA) signaling pathways are highlighted. The circadian clock fulfills a crucial role at the heart of cellular networks and the bilateral relation between sugar signaling and the clock is discussed. It is proposed that important factors controlling plant growth (DELLAs, PIFs, invertases and trehalose- 6-phosphate or T6P) might fulfill central roles in the transition to flowering as well. The emerging concept of ‘sweet immunity’, modulated by the clock, might at least partly rely on a sucrose-specific signaling pathway that needs further exploration.